Perbandingan Sintesis Nanoselulosa dari Limbah Kertas Saring Praktikum dengan Hidrolisis Asam Anorganik dan Organik sebagai Upaya Pengelolaan Limbah Laboratorium - Istiqomah, Zahrotul; Rahmantiyoko, Agus; Sunarmi, Sri (Jurnal Pengelolaan Laboratorium Pendidikan, 2025)
Nanocellulose is one of the nanoparticles that is widely used in various applications such as the base material of bioplastics and nanocomposites. Because nanocellulose has several properties including high mechanical and high thermal properties, transparency and lightness. Nanocellulose is generally isolated from lignocellulosic biomass, which contains high cellulose, is abundant and relatively cheap. This study aims to synthesize nanocellulose from filter paper practicum waste in the Fundamental Chemistry Laboratory of ITS, which has not been optimally used. The synthesis method used is acid hydrolysis, namely inorganic and organic acids. The results of the nanocellulose synthesis in this study are as follows: hydrolysis with inorganic acid hydrochloric acid and sulfuric acid is round like a ball with an average diameter size below 100 nm, for hydrochloric acid the average diameter is 53,14 nm and sulfuric acid 42,08 nm, while hydrolysis with organic acid, formic acid and citric acid, nanocellulose is shaped like a rod with an average diameter of 36,80 nm for formic acid and 46,23 nm for citric acid.